(3QhV GdESYGO HJTWjQ HGfJ SYGOs - (3CHh GdfUQ GdWQGHdSis; (3cYH Hf RgjQ , CHh GdeZQH,J (B26 (3g` s
(3ChdgG (B:s
(3HGfJ SYGO abdHi Gdjhe eJHhd eOdg MGFQ hGdYbd eYbhd s
(3BNQgG (B:s
(3heGdge Yf dbGA GdMQH ef edd heGdge Yf MjGV GdehJ Jgdjd ? s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdJGSY YTQs
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B226s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1329s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdCSJGP GdOcJhQ GSMGb ehSi GdMSjfi GdNGUI s
Keywords: (3Gdabg GdTGaYjs